Terrorism and Tourism: A Systematic Review of Empirical Literature - NARADDA GAMAGE, Sisira Kumara; ILLANGARATHNE, S.K.; KUMUDUMALI, S. H. T.; NEDELEA, Alexandru-Mircea (Revista de turism - studii și cercetări în turism, 2020)
The paper systematically discusses the literature on terrorism and tourism between the years 2010 to 2019. The Scopus database was selected to make the literature search process transparent, and the literature survey was based on terrorism and tourism as the keywords. The PRISMA 2009 helped the selection and exclusion process. During literature classification, the final 37 articles with at least one citation for the review were arranged in an excel sheet to find the gap and directions of terrorism and tourism. The results revealed literature on the nature of the relationship between terrorism and tourism, critical challenges related to terrorism, regional effects of terrorism on tourism, and terrorism impact preventing strategies. The systematic review recommends that future research must focus on critical disputes related to terrorism, and suitable strategies to prevent terrorism